2017
DOI: 10.1002/14651858.cd009761.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for preventing high altitude illness: Part 1. Commonly-used classes of drugs

Abstract: Background High altitude illness (HAI) is a term used to describe a group of cerebral and pulmonary syndromes that can occur during travel to elevations above 2500 metres (˜ 8200 feet). Acute hypoxia, acute mountain sickness (AMS), high altitude cerebral oedema (HACE) and high altitude pulmonary oedema (HAPE) are reported as potential medical problems associated with high altitude. In this review, the first in a series of three about preventive strategies for HAI, we assess the e ectiveness of six of the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 168 publications
1
36
0
4
Order By: Relevance
“…The CA inhibitor ACT has been used to prevent blood pressure elevation in high‐altitude sickness (Nieto Estrada et al, ; Parati et al, ). ACT is also known to reduce breathing disturbances at both sea level and high altitude (Edwards et al, ; Javaheri, ; Nussbaumer‐Ochsner et al, ; Tojima et al, ; Whyte, Gould, Airlie, Shapiro, & Douglas, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The CA inhibitor ACT has been used to prevent blood pressure elevation in high‐altitude sickness (Nieto Estrada et al, ; Parati et al, ). ACT is also known to reduce breathing disturbances at both sea level and high altitude (Edwards et al, ; Javaheri, ; Nussbaumer‐Ochsner et al, ; Tojima et al, ; Whyte, Gould, Airlie, Shapiro, & Douglas, ).…”
Section: Discussionmentioning
confidence: 99%
“…CA activity appears to increase during episodes of environmental stress, such as hypoxia at high altitude (Juel, Lundby, Sander, Calbet, & Hall, ) and intense exercise (Tokuda, Iiboshi, Suenaga, & Otsuji, ). Drugs with CA inhibitory properties have been widely used in conditions such as glaucoma and high‐altitude disease (Nieto Estrada et al, ; Scozzafava & Supuran, ). We have previously reported that whole blood CA activity was linearly associated with apnea severity and diastolic blood pressure in a cohort of patients with mild‐to‐severe OSA (Wang, Eskandari, Zou, Grote, & Hedner, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Samkvaemt Cochrane-safngreiningu frá árinu 2017 virtist lyfið draga verulega úr líkum á háfjallaveiki með áhaettuhlutfall 0,47 (95%-ÖB: 0,39-0,56). 51 Alls var um að raeða 16 rannsóknir með samtals 2301 þáttakendum. Í tiltölulega fáum rannsóknanna hefur aukaverkunum verið lýst, eða í 5 þeirra sem tóku til 789 þátttakenda og var þar meðal annars lýst umtalsverðri aukningu á náladofa (áhaettuhlutfall 5,53, 95%-ÖB: 2,81-10,88).…”
Section: Haeðarveiki Og Haeðarheilabjúgurunclassified
“…7,54,55 Cochrane-safngreining sem birtist árið 2017, og tók til fjögurra rannsókna með samtals 176 þátttakendum, sýndi að lyfið dró ekki marktaekt úr áhaettu á háfjallaveiki en þó vantaði lítið upp á að tölfraeðilegri marktaekni vaeri náð (áhaettuhlutfall 0,60, 95%-ÖB: 0,36-1,00). 51 Ekki er ráðlegt að taka sykurstera í meira en 10 daga samfleytt vegna haettu á aukaverkunum og mikilvaegt er að hafa í huga að einkenni haeðarveiki geta komið fram aftur þegar lyfjagjöf er haett. 56 Ýmis önnur lyf hafa verið rannsökuð með tilliti til þess hvort þau fyrirbyggi haeðarveiki en í þeim hópi eru helst magnesíum sítrat og Ginkgo biloba.…”
Section: Haeðarveiki Og Haeðarheilabjúgurunclassified